2017
DOI: 10.3851/imp3237
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Prevalence of Baseline Resistance-Associated Polymorphisms and Resistance Mutations in HCV against Current Direct-Acting Antivirals

Abstract: In this study, we show the presence and prevalence of RAPs and RMs in DAA treatment-naive patients against currently used DAAs or DAAs in clinical trials. Our study suggests that RAPs and RMs profiling of HCV patients should be performed before the start of the therapy. Our results should be relevant especially in low- and middle-income countries, where the patients have a large variation of GTs and subtypes, and where the generic HCV treatment is now increasingly available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…( 35 ) This difference may reflect geographic variations in baseline RAS prevalence as we have previously observed a 4% prevalence of H58 RAS among untreated Australian patients with genotype 1a ( 36 ) compared to 0%‐2% in global and European patients. ( 16,37 ) In contrast to the wide range of RASs for genotype 1a, patients with genotype 3a were more likely to have a single NS5A RAS, with Y93H found in 72%. This is similar to the 66% prevalence in the European study ( 30 ) and may reflect a relatively high baseline prevalence of Y93H (9%) among patients with genotype 3a who are treatment naive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 35 ) This difference may reflect geographic variations in baseline RAS prevalence as we have previously observed a 4% prevalence of H58 RAS among untreated Australian patients with genotype 1a ( 36 ) compared to 0%‐2% in global and European patients. ( 16,37 ) In contrast to the wide range of RASs for genotype 1a, patients with genotype 3a were more likely to have a single NS5A RAS, with Y93H found in 72%. This is similar to the 66% prevalence in the European study ( 30 ) and may reflect a relatively high baseline prevalence of Y93H (9%) among patients with genotype 3a who are treatment naive.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the 66% prevalence in the European study ( 30 ) and may reflect a relatively high baseline prevalence of Y93H (9%) among patients with genotype 3a who are treatment naive. ( 37 ) The very high prevalence of Y93H among treatment failures is clinically important as Y93H confers high levels of resistance against most NS5A inhibitors, with a 3,500‐fold reduction in half‐maximal effective concentration (EC50) for daclatasvir and over 700‐fold reduction in EC50 for velpatasvir. ( 38 )…”
Section: Discussionmentioning
confidence: 99%
“…The NS5A RAS Y93H mutation/polymorphism is found quite often (5-10%) at baseline in DAA-treatment-naïve patients with GT 3 (with regard to subtype 3a) using the population sequencing method [15]. This RAS possesses a high fold in vitro resistance of >2000 to daclatasvir (DCV) and >700 to velpatasvir (VEL) used for treatment of GT 3 infection [16][17][18]. This was further revealed in clinical studies, the ALLY-3 study showed that 33% without liver cirrhosis and 75% with liver cirrhosis of the GT 3 patients with baseline RAS Y93H failed 12-week treatment with DCV plus sofosbuvir (SOF) [19].…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence of variants C445F, A553V and S556G were found in both GTs 2b and 3a. The variants C445F and S556G have also been previously reported as baseline polymorphisms with natural prevalence ranging from 96 to 100% for GT 2 and from 97.1 to 100% for GT 3 [7,42,45,46]. Additionally, the natural prevalence of the variant A553V was reported to be 96% for GT 2 and 97.1% for GT 3[46].…”
Section: Discussionmentioning
confidence: 97%
“…The variants C445F and S556G have also been previously reported as baseline polymorphisms with natural prevalence ranging from 96 to 100% for GT 2 and from 97.1 to 100% for GT 3 [7,42,45,46]. Additionally, the natural prevalence of the variant A553V was reported to be 96% for GT 2 and 97.1% for GT 3[46]. The variant A553V is associated with a high level (> 100-fold increase in effective concentration 50 ) of resistance against dasabuvir in GT 1b replicon assay [20].…”
Section: Discussionmentioning
confidence: 99%